Percutaneous management of chronic total occlusion of the portal vein: a retrospective analysis of technical aspects and outcomes - Ludovico Dulcetta; Paolo Marra; Riccardo Muglia; Francesco Saverio Carbone; Mauro Viganò; Angelo Di Giorgio; Lorenzo D’Antiga; Stefano Fagiuoli; Sandro Sironi (CVIR Endovascular)
Abstract Background Chronic total occlusion (CTO) of the portal vein is one of the main causes of portal hypertension, which may result in life-threatening complications often managed by interventional radiology (IR). The aim of this study is to report the innovative experience with percutaneous revascularization therapy in the management of portal vein CTO in paediatric and adult patients. Materials and methods From January 2020 to December 2023 consecutive paediatric and adult patients with severe portal hypertension resulting from portal vein CTO who underwent attempts at percutaneous recanalization were retrospectively reviewed. Technical aspects including the percutaneous approach, portal vein stenting, transjugular intrahepatic portosystemic shunt (TIPS) creation, varices embolization and clinical outcomes including adverse events and control of portal hypertension were analyzed. Technical success was defined as at least partial restoration of the portal vein patency at the final angiogram. Clinical success was defined as the improvement of clinical-laboratory signs of portal hypertension and control for variceal bleeding. Results Fifteen patients (median age = 21 years, range = 59 years; 10 males; 5 children) with portal vein CTO underwent a total of 25 percutaneous revascularization procedures. Nine patients (60%; 5 children, 4 adults) were liver transplant recipients. All patients except one had cavernous transformation of the extra-hepatic portal vein, involving the spleno-mesenteric confluence in 5 cases. Technical success was achieved in 13/15 (87%) patients of whom 8 had portal revascularization through the placement of an extra-hepatic stent; indeed, in six cases, a TIPS was performed to achieve sustained portal vein patency. Embolization of varices and/or cavernoma was performed in 12 patients. Adverse events occurred in 2/15 (splenic artery perforation and hemoperitoneum, one each) managed without sequelae. Technical success led to clinical success in all the 13/15 (87%) cases, with a median follow-up of 20 months (IQR 4–34 months). Conclusion CTO can be managed effectively by interventional radiology. Restored portal flow physiology alone is possible in most patients, while TIPS may be required in a small proportion of them, to prolong portal vein patency and control portal hypertension.